Perancangan Sistem Identifikasi Berdasar Proses Fabrikasi Menggunakan Visual Basic For Application (VBA) - Andi M. Yusuf (Celebes Engineering Journal, 2020)
This study aims to design an Identification System based on the Fabrication Process using Visual Basic for Application (VBA) and has two main functions, namely the input and search functions. Entering component data and coding (Code Identification) on the ship is an input function. Searching for item data and component code with manufacturing process keywords in accordance with the contents of the code so that components are grouped based on one of the fabrication process keywords is a search function.